Lexemas on Science and Education in Yusuf Hos Hojib's Work "Kutadgu Bilig" - Raxmatullaeva. D. Sh (International Journal on Integrated Education, 2021)
This article analyzes the lexical-semantic lexical units of "science-enlightenment" used in Yusuf Khos Hajib's work "Qutadg'u bilig".